Psychological aspects of experiencing war stress by students when learning a foreign language - Kresan, O.; Smolianinova, S.; Kresan, T. (My University, 2023)
The article deals with the psychological aspects of experiencing war stress by the students when learning a foreign language. Teaching students in Ukraine nowadays is associated with a high degree of stress. This especially applies to learning a foreign language, which already involves a certain level of stress, as it requires performing a significant number of interactive tasks, constant communication and involves foreign language acquisition. In order to research this issue, the authors analyzed the main approaches to the study of stress in modern psychology as well as physiological and mental state of students while learning a foreign language for specific purposes. The article outlines the didactic and psychological features of foreign language learning and its principles. During practical foreign language classes with students, we conducted an empirical study using the method of included longitudinal observation, chosen in order to avoid psychological traumatization and retraumatization, as well as providing emotional support in educational environment that is familiar to them. As a result of the study, three groups of students have been distinguished according to the way the stress symptoms are revealed: manifestations of minor, moderate and severe stress. The authors analyzed characteristics of their cognitive activity while learning a foreign language and motivation to study. The article presents the author's model of a person's psychological reactions to stress which proves that stressors can affect the human body and mental health in two ways, causing both emotional exhaustion and personal growth, leading to the enrichment of life experience and helping to find meanings in life.
Keywords: stress; emotional support; learning a foreign language; personal growth; emotional exhaustion